Clinical and Histopathologic Features of Colorectal Adenocarcinoma in Crohn's Disease. Issue 7 (August 2018) - Galata, Christian; Hirsch, Daniela; Reindl, Wolfgang; Post, Stefan; Kienle, Peter; Boutros, Michael; Gaiser, Timo; Horisberger, Karoline
Abstract : Goals: The aim of this study was to assess the histopathologic characteristics of colorectal carcinomas (CRC) in patients with Crohn's disease (CD). Background: A higher frequency of microsatellite instability (MSI) is seen in mucinous compared with nonmucinous CRC which suggests that its pathogenesis involves distinct molecular pathways. Several publications reported a higher percentage of mucinous adenocarcinoma in CD patients with CRC. So far, there has been no investigation of MSI in CD patients with mucinous CRC. Study: The medical records of patients who underwent surgery for CRC were reviewed and those with a history of CD identified. The data of histologic classification and MSI status of the tumor were investigated. Results: Fourteen patients with CD-associated CRC were identified (5 female, 9 male) resulting in 20 CRC in total. Histologic investigation revealed 7 adenocarcinomas without a mucinous or signet ring cell component. All other CRCs harbored a mucinous (n=11) and/or signet ring cell (n=6) component. All tumors assessed for MSI were found to be microsatellite stable. Conclusions: Our data indicate that CRCs with signet ring cell and mucinous components were much more common in patients with CD than in patients with sporadic CRC. This observation suggests that CRC in CD represent an own entity with distinct histopathologic and molecular features. This may implicate potential consequences for diagnosis and therapy of CRC in CD in the future as well as new factors to identify patients with an increased risk for developing CRC in CD.